1998
DOI: 10.1042/bj3300437
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the rat salivary-gland B1-immunoreactive proteins

Abstract: The B1-immunoreactive proteins (B1-IPs) are major secretory products of rat submandibular gland acinar-cell progenitors, and are also produced by neonatal and adult rat sublingual and parotid glands. In order to characterize the B1-IPs, we have previously isolated cDNA clones encoding rat parotid secretory protein (PSP; the predominant parotid B1-IP) and the related clone ZZ3, which is developmentally regulated in the neonatal submandibular gland. The remainder of the B1-IPs were uncharacterized. This report d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 32 publications
4
38
0
Order By: Relevance
“…Pronase reacted with the electron-dense portion of Type I-III granules; however, immunohistochemical staining with anti-amylase antibody showed almost no positive reaction in these granules (data not shown). Ball et al (1993) and Mirels et al (1998) also demonstrated that highly electron-dense granules in secretory cells from the early postnatal mouse parotid gland, and in cells from the serous demilune of the mature rat sublingual gland contain protein B1. Furthermore, Wolff et al (2002) showed that by age 20 days in utero, mucous cells in the rat sublingual gland have granules labeled with antimucin, and serous cells have numerous granules containing CSP-1, SMGB, PSP, and SMGD.…”
Section: Discussionmentioning
confidence: 93%
“…Pronase reacted with the electron-dense portion of Type I-III granules; however, immunohistochemical staining with anti-amylase antibody showed almost no positive reaction in these granules (data not shown). Ball et al (1993) and Mirels et al (1998) also demonstrated that highly electron-dense granules in secretory cells from the early postnatal mouse parotid gland, and in cells from the serous demilune of the mature rat sublingual gland contain protein B1. Furthermore, Wolff et al (2002) showed that by age 20 days in utero, mucous cells in the rat sublingual gland have granules labeled with antimucin, and serous cells have numerous granules containing CSP-1, SMGB, PSP, and SMGD.…”
Section: Discussionmentioning
confidence: 93%
“…It is well known that many salivary proteins undergo complex posttranslational modification, including glycosylation, and it is assumed that this has a major effect on their function . It is also note-worthy that rodent psp and smgb (Mirels et al 1998), as well as bovine bsp30a and b (Haigh et al 2008) have been shown to be N-glycosylated.…”
Section: Multiple Splunc2 Bands Are Detectable In Human Salivamentioning
confidence: 99%
“…Immunoreactivity for parotid secretory protein (PSP), a salivary protein co-expressed with Smgb in the developing rat submandibular gland (Ball et al, 1988;Mirels et al, 1998), was used to identify proacinar and maturing acinar cells. Three days after birth, the mouse submandibular gland remained immature.…”
Section: Time Course Of Tumor Initiation and Progressionmentioning
confidence: 99%
“…These mice contain a transgene in which Tag expression is targeted to intercalated ducts by regulatory sequences derived from the rat submandibular gland secretory protein b (Smgb) salivary protein gene (Gupta et al, 2000). Smgb is normally expressed in neonatal submandibular gland proacinar cells, and in a subset of intercalated duct cells of the adult gland (Ball et al, 1988;Mirels et al, 1998;Moreira et al, 1990). The Smgb-Tag transgene is expressed in these cells, but also in some neonatal submandibular gland secretory terminal tubule cells, and in the majority of intercalated duct cells.…”
mentioning
confidence: 99%